Financial literacy of professionals working in banking institutions (Research, Society and Development, 2023)
Professionals who work in banking institutions undergo qualification requirements, through graduation and certification, regarding activities related to finance, therefore, this research aims to identify how this professional conducts his personal finances. Financial literacy consists of three constructs: financial attitude, financial behavior and financial knowledge, the latter being characterized as a synonym for financial education. The research is quantitative, with data collected through a questionnaire and analyzed in a statistical and bivariate way, to meet the research objectives. The subjects that make up the sample are employees of three private banking institutions present in the city of Foz do Iguaçu, in the state of Paraná. The construction of the three constructs allowed the verification that the construct financial knowledge is the most verified with a high level, therefore, the constructs financial attitude and financial behavior can be raised through the increase of the individual's concern with the future, taking care of the present and reserving an amount of your monthly acquired money. The most common investment found was savings, even among professionals from banking institutions. Debts were also found, but all paid up to date, according to the agreed dates, with no individuals in default.